Comparing Gait Variability Between Deaf and Normal-Hearing Children After Proprioception Training - Fatemeh Yaghoubi Hamraz; Mahdi Majlesi (Biyumikānīk-i varzishī, 2020)
Objective: Gait variability is an important feature in clinical treatment of people with walking problems. Since the gait variability has not been yet evaluated among deaf people, the purpose of this study was to evaluate the gait variability in deaf children and compare it with normal-hearing peers. Methods: The study population consists of deaf and normal-hearing children living in Hamedan, Iran. Of these, 10 deaf (aged 8-14 years) and 10 with normal hearing matched for age and anthropometric characteristics volunteered to participate in the study. The 3D Vicon motion analysis system was used to measure the kinematic gait parameters in subjects. Paired sample t-test was used for within-group comparison and independent sample t-test for between-group comparison. Statistical analysis was performed in SPSS software by considering a significance level of P<0.05. Results: The gait variability after proprioception training decreased in deaf children, but this change was not statistically significant (P>0.05). There was no significant difference between the two groups before and after the training (P>0.05). Conclusion: It is suggested that balance exercise with an emphasis on proprioception training be included in the physical education program of deaf children.